Linguistic Aesthetics In The Podshort: A Study Of Code-Switching And Code-Mixing On “Kesel Aje” - Muhammad Rizal Alma; Shamsi Ara Huda; Ahmed Mohamed Zanghar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the forms of code-mixing in the YouTube Shorts content of the Podcast Kesel Aje channel and to explain its implementation regarding language aesthetics, specifically in the selection of appropriate vocabulary. Methodology: This qualitative research used the human instrument for data collection. Data in the form of words and phrases were gathered from Podcast Kesel Aje YouTube Shorts videos from September–October 2023 using library techniques, observation, and note-taking. Main Findings: The research identified 181 instances of code-mixing, consisting of 176 at the word level and 5 at the phrase level. No code-switching was found. The dominant form was word-level code-mixing, primarily involving Indonesian mixed with English, Chinese, Javanese, and Betawi. Novelty/Originality of this study: This study provides new insights by specifically analyzing code-mixing in the short-form video format (YouTube Shorts) of a popular youth-oriented podcast. It also traces the etymological origin of frequently used pronouns (lu/gua) to Chinese, challenging the common assumption of Betawi origin.